2013
DOI: 10.1002/jmv.23505
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for penile infection by high‐risk human papillomavirus among men infected with HIV

Abstract: This study aimed to determine the prevalence of and risk factors for high-risk human papillomavirus (HPV) genital infection and precursor lesions of penile cancer among patients infected with human immunodeficiency virus (HIV). In total, 276 men with a mean age of 34.6 years were included. All participants were subjected to peniscopic examination under magnification, collection of genital exfoliated cells for detecting HPV types using Hybrid Capture, and biopsy surgery of clinically observable lesions and acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…Most studies in adults find higher rates of HPV in those persons with low CD4 counts. 20,21 Although we found no such association with CD4 counts, our population overall had high CD4 counts limiting any comparisons. The higher prevalence observed in the girls was not completely unexpected since the external genitalia of girls appears more vulnerable to HPV infections, including genital warts.…”
Section: Discussioncontrasting
confidence: 61%
“…Most studies in adults find higher rates of HPV in those persons with low CD4 counts. 20,21 Although we found no such association with CD4 counts, our population overall had high CD4 counts limiting any comparisons. The higher prevalence observed in the girls was not completely unexpected since the external genitalia of girls appears more vulnerable to HPV infections, including genital warts.…”
Section: Discussioncontrasting
confidence: 61%
“…For instance, one study showed that in PWH, having a CD4 + less than 200 cell/μl was significantly associated with a higher risk of anogenital warts and anal high-grade squamous intraepithelial lesions/cancer [26]. Another study showed that in men living with HIV, CD4 + less than 200 cell/μl was significantly associated with high-risk HPV infection [12], which is highly associated with HPV-related cancers. These findings reflect the vital role of ART in maintaining viral suppression and restoring immune function, thereby leading to a reduction in the risk of developing HPV-associated cancers, including penile cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HIV could be considered an indirect carcinogen because it facilitates development of some cancers via immune suppression [11]. HPV infection contributes to carcinogenesis in about 50% of penile cancers [12], and HIV infection is associated with increased prevalence and persistence of HPV infection as well as reduced HPV clearance at different anatomic sites [13,14]. Consequently, HPV co-infection in PWH likely contribute to their increased risk of HPV-related cancers.…”
Section: Introductionmentioning
confidence: 99%